2006
DOI: 10.1152/ajplung.00334.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of endogenous β-adrenergic tone on lung fluid balance in acute bacterial pneumonia in mice

Abstract: A. Matthay. Protective effect of endogenous ␤-adrenergic tone on lung fluid balance in acute bacterial pneumonia in mice. Am J Physiol Lung Cell Mol Physiol 290: L769 -L776, 2006. First published November 11, 2005 doi:10.1152/ajplung.00334.2005.-Some investigators have reported that endogenous ␤-adrenoceptor tone can provide protection against acute lung injury. Therefore, we tested the effects of ␤-adrenoceptor inhibition in mice with acute Escherichia coli pneumonia. Mice were pretreated with propranolol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
3
29
1
Order By: Relevance
“…Consistent with these studies (45,46), plasma epinephrine levels were elevated during VILI ( Figure 11A). However, no differences between A2BAR -/-mice or their corresponding control mice were observed, suggesting that A2BAR signaling is not involved in VILI-associated increases in plasma epinephrine ( Figure 11B).…”
Section: Figuresupporting
confidence: 83%
“…Consistent with these studies (45,46), plasma epinephrine levels were elevated during VILI ( Figure 11A). However, no differences between A2BAR -/-mice or their corresponding control mice were observed, suggesting that A2BAR signaling is not involved in VILI-associated increases in plasma epinephrine ( Figure 11B).…”
Section: Figuresupporting
confidence: 83%
“…Experimental and clinical studies have shown that the cAMP-mediated stimulation of CFTR-dependent alveolar fluid clearance by endogenous or exogenous ␤ 2 AR agonists is one of the major mechanisms that prevent the flooding of the airspaces after onset of ALI (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)23). However, despite the massive release of catecholamines associated with several condi- B, prolonged exposure (6 h) to TGF-␤1 inhibits the epinephrine-dependent PKA activation in polarized rat primary ATII cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant efforts have been made to pharmacologically up-regulate alveolar fluid clearance to reverse the progression of lung injury, these approaches have not been successful (4). ␤ 2 -Adrenergic receptor (␤ 2 AR) agonists have been shown to enhance alveolar epithelial fluid transport via a cAMP-dependent mechanism under physiological conditions (5)(6)(7)(8)(9)(10)(11) and in various experimental models of ALI (12)(13)(14) as well as in one small prospective study in ALI patients (15). However, one of the main limitations of this therapeutic approach is that ␤-adrenergic agonist hyporesponsiveness has been reported in some experimental models of ALI (16,17), although none of the critical mediators of ALI have yet been shown to inhibit the ␤-adrenergic-stimulated fluid transport of the distal lung epithelium.…”
Section: Acute Lung Injury (Ali)mentioning
confidence: 99%
“…There is a great body of experimental data indicating that specific and nonspecific b-agonists enhance AFC in experimental models of cardiogenic and noncardiogenic pulmonary edema (1, 9, 61). Recent data suggest that preservation of b-adrenergic receptor signaling attenuates loss of endothelial cell barrier function in mice with severe bacterial pneumonia (98). Stimulation of b-adrenergic receptors is also capable of preventing hypoxia-induced reduction in alveolar active Na 1 transport and fluid clearance in rats (99).…”
Section: Other Functionsmentioning
confidence: 99%